The Holy spirit, the church and daily life : a theological search for an integrated pneumatology in the light of Chewa views of the spirit - Siwinda, Julius Chikhutu (Stellenbosch : Stellenbosch University, 2017)
Thesis (MTh)--Stellenbosch University, 2017.